Examining Types of Fatigue Among Individuals with ME/CFS - Jason, Leonard; Jessen, Tricia; Porter, Nicole; Boulton, Aaron; Gloria-Njoku, Mary (Disability Studies Quarterly, 2009)
Severe, persisting fatigue is a prominent symptom of Myalgic Encephalomyelitis/chronic fatigue syndrome (ME/CFS), but individuals with this illness frequently report the occurrence of unique fatigue states that might be different from conventional symptoms of fatigue. The present study attempted to assess a comprehensive set of fatigue symptoms that have been commonly reported among patients with ME/CFS. A 22-item fatigue questionnaire was developed and administered to 130 persons diagnosed with ME/CFS and 251 controls. Adequate scale reliability was found. Factor analyses revealed a five-factor structure for participants with ME/CFS but only a one factor solution for the control group. The new scale was also contrasted with other more traditional scales developed to measure fatigue. Findings suggest that individuals with ME/CFS experience different types of fatigue than what are reported in the general populations.